Students’ perceptions of AI integration in enhancing autonomous learning - Navisatul Izzah; Fadhil Djibran; Kinanti Resmi Hayati; Dian Rachmatika (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2026)
The rapid development of generative Artificial Intelligence (AI) has transformed multiple domains, including education, offering new opportunities for supporting student learning and autonomous study. This study investigates students’ perceptions of generative AI as a supplementary learning tool and explores how it contributes to academic performance, autonomous earning, and access to information. Using a quantitative approach, data were collected from 50 students at UPN “Veteran” Jawa Timur through an online survey, covering frequency of AI use, perceived helpfulness, quality of information, satisfaction, and learning outcomes. The findings reveal that the majority of students use AI frequently to find references, additional learning materials, and answers to specific questions. Most respondents perceive AI as effective in improving their academic results. Students reported high satisfaction, with no respondents expressing dissatisfaction. Despite these positive perceptions, concerns were raised regarding accuracy, reliability, and limitations in specialized subject areas, highlighting the necessity of critical evaluation and responsible use. Future research should expand to larger, more diverse student populations, investigate educators’ perspectives, and conduct longitudinal studies to examine the long-term impact of AI on critical thinking, creativity, and academic development. Overall, while generative AI presents significant potential to enhance autonomous learning, its benefits are maximized only when combined with careful oversight and active engagement in the learning process.